On the Origin of Iranian-Speaking Nomads of the Eurasian Steppes in the Light of Human Population Genetics - Pstrusińska, Jadwiga (Anabasis. Studia Classica et Orientalia, 2014)
We learn from the history and geography of human genes regarding the origin of the so-called Iranian people, the Iranian-speaking Nomads of the Eurasian Steppes inclusive, among whom scholars traditionally include Scythians, Sarmatians and Alans, that they cannot necessarily be treated as belonging in the past to an Indo-Iranian community speaking an Indo-Iranian language.